Notes on Uraria (Leguminosae: Papilionoideae: Desmodieae) from Thailand and Vietnam - Tokaew, Worachat; Chantaranothai, Pranom; Balslev, Henrik; Wangwasit, Kamolhathai (Thai Forest Bulletin (Botany), 2020)
Uraria balansae and U. barbaticaulis are newly recorded from Thailand. Uraria pseudoacuminata is reported as new for Vietnam. Descriptions, ecological data, vernacular names, photographs and distribution maps are provided. Uraria balansae is lectotypified.